Kajian Pengembagan Sport Tourism di Sungai Kedung Jati, Imogiri - Prabowo, Hanan Okta; Rahmawan, Fajar Tri; Prasetya, Arif Bagus; Ekadhana, Chriastopher Arsenio; Anshori, Luthfi Al; Arifin, Imam Nur; Hadiono, Hadiono (JURNAL NASIONAL PARIWISATA, 2025)
The tourism sector plays an important role in the Indonesian economy, and its contribution has increased rapidly in recent years. Tourism is considered a major source of income for the region. The development of tourism in the region or rural areas is an attraction for research to make the tourist spot more advanced and developed. One of them is the Kedung Jati tourist village in Imogiri Bantul. This study aims to find out more about the tourism potential in the village using a SWOT analysis with a focus on the growth of sports tourism and highlighting the importance of sports tourism in improving the local economy and preserving culture. This study uses a qualitative descriptive method with primary and secondary data to obtain their perspectives and experiences related to sports tourism in Kedung Jati tourism. The findings show that although this area has natural beauty, there is a lack of community involvement in sustainable tourism development and progress. Future research can explore the potential for sustainable nature tourism to maintain management and maintain its ecosystem.